Methionine-mediated synthesis of magnetic nanoparticles and functionalization with gold quantum dots for theranostic applications - Jagminas, Arūnas; Mikalauskaitė, Agnė; Karabanovas, Vitalijus; Vaičiūnienė, Jūrate (Beilstein Journal of Nanotechnology, 2017)
Biocompatible superparamagnetic iron oxide nanoparticles (NPs) through smart chemical functionalization of their surface with fluorescent species, therapeutic proteins, antibiotics, and aptamers offer remarkable potential for diagnosis and therapy of disease sites at their initial stage of growth. Such NPs can be obtained by the creation of proper linkers between magnetic NP and fluorescent or drug probes. One of these linkers is gold, because it is chemically stable, nontoxic and capable to link various biomolecules. In this study, we present a way for a simple and reliable decoration the surface of magnetic NPs with gold quantum dots (QDs) containing more than 13.5% of Au+. Emphasis is put on the synthesis of magnetic NPs by co-precipitation using the amino acid methionine as NP growth-stabilizing agent capable to later reduce and attach gold species. The surface of these NPs can be further conjugated with targeting and chemotherapy agents, such as cancer stem cell-related antibodies and the anticancer drug doxorubicin, for early detection and improved treatment. In order to verify our findings, high-resolution transmission electron microscopy (HRTEM), atomic force microscopy (AFM), FTIR spectroscopy, inductively coupled plasma mass spectroscopy (ICP-MS), and X-ray photoelectron spectroscopy (XPS) of as-formed CoFe2O4 NPs before and after decoration with gold QDs were applied.
Keywords: functionalization; gold; magnetic nanoparticles; quantum dots; theranostics